ANALYSIS OF HIGH SCHOOL STUDENTS’ MISCONCEPTION IN ENERGY USING ORDERED AND REASONING MULTIPLE CHOICE - Nurul F. Sulaeman; Laili Komariyah; Siska Fitri Yani (FKIP Universitas Jember, 2018)
Abstract While some misconceptions already believed by students, it will resist changing. Therefore,the earlier diagnosis of students’ misconceptions becomes crucial. This study determinedthe misconceptions experienced by students in energy and evaluated the use of OrderedMultiple Choice (OMC) and Reasoning Multiple Choice (RMC) test to measure it. Thesample in this study was two classes at SMA N 1 Samarinda that was taken by purposivesampling technique. The samples were had relatively similar capability in physics, taughtby the same teacher with same teaching method. From the result, it is found that there aresome misconceptions experienced by the students. In the first class, percentagemisconception measured by OMC are level 1